2021
DOI: 10.3390/biom11020163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Humanizing Mutations on the Stability of the Llama Single-Domain Variable Region

Abstract: In vivo clinical applications of nanobodies (VHHs) require molecules that induce minimal immunoresponse and therefore possess sequences as similar as possible to the human VH domain. Although the relative sequence variability in llama nanobodies has been used to identify scaffolds with partially humanized signature, the transformation of the Camelidae hallmarks in the framework2 still represents a major problem. We assessed a set of mutants in silico and experimentally to elucidate what is the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
(65 reference statements)
2
23
0
Order By: Relevance
“…There are several examples demonstrating the feasibility of this approach, but these are still the results of case-by-case projects that require a major input from specialized researchers and often require access to structural information [9][10][11][12]. On the other hand, we recently confirmed that publicly accessible algorithms that require minimal data inputs can rapidly and effectively help in the identification of protein variants that exhibit astonishingly higher yields than the original sequences [13].…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…There are several examples demonstrating the feasibility of this approach, but these are still the results of case-by-case projects that require a major input from specialized researchers and often require access to structural information [9][10][11][12]. On the other hand, we recently confirmed that publicly accessible algorithms that require minimal data inputs can rapidly and effectively help in the identification of protein variants that exhibit astonishingly higher yields than the original sequences [13].…”
Section: Introductionmentioning
confidence: 79%
“…The A10 mutG0 clone (6.9 mg/L medium) produced roughly 30% more than A10 wt (5.2 mg/L), but both A10 mutKG and A10 mutKG.1 had higher production yields (9.6 and 12.8 mg/L, respectively). Interestingly, whereas the mutations from “human-like” to the canonical “llama” residues in the framework of A10 wt did not result in higher production yields [ 12 ], the mutant with glycine insertion (A10 mutKG.1) profited from the “camelization” of the original partially humanized sequence (A10 mutKG). In contrast, the further mutation present in A10 mutKG.2 (K/L in CDR3) had a remarkable negative effect on the nanobody yield, suggesting that the wt CDR3 was already stable and did not require further optimization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations